PELAKSANAAN KADERISASI PEREMPUAN PARTAI GERINDRA KOTA PEKANBARU TAHUN 2014-2019 - Rizkia Krizma Cahya Ramadhani; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Gerinda party is a new party which, according to its development in a short time, has management at all levels, both provincial and district/city to sub-district and village levels. at this time all parties including gerindra are faced with various problems regarding the problem of a weak recruitment system, an ineffective regeneration system, resulting in the lack of representation of women sitting in the legislature. the cadre of women in political parties is an important issue, because every political party, both in the management structure and in the nomination of legislative candidates, must place thirty percent (30%) of women's representation.The purpose of this study was to determine the implementation of the female cadre of the gerindra party in pekanbaru city in 2014-2019. the research method used in this research is descriptive qualitative with interview and documentation data collection techniques.The results of this study indicate that the implementation of the female cadre of the gerindra party in pekanbaru city in 2014-2019 was carried out in two stages: first, cadreization education and training, second, advanced cadreization. the regeneration process for the dpc gerindra party in pekanbaru city is carried out in stages with three categories, namely driving cadres, middle cadres and young cadres. barriers to the implementation of the female cadre of the gerindra party in pekanbaru city in 2014-2019, among others, are the lack of interest in women in the world of politics and supported by public perceptions that tend to be biased towards limiting the role of women in household matters, so that the majority of votes in the general election are won by men. -male. keywords: implementation of women's cadre, elections, political parties